南洋想象与建构 ：以《南洋画报》为考察对象 = Imagining the modern Nanyang : a case study of “Nanyang Monthly” - 郭美堯 Kuo Mei Yao (2018)
南洋地区因为与中国之间具有深厚的历史渊源，使具有地域性的、想象性概念的“南洋”一词，一直以来必须在和中国的相互参照中才能获得意义。二战以后，殖民政府相继退出南洋地区，居于南洋的人们需要重新定义自己身份、认识南洋国家之间的关系，认同的需求于是变得急迫。班纳迪克·安德森指出，印刷出版物作够使形塑民族成为可能，在这时候面世的刊物，就別具时代意义。《南洋画报》作为一个知识输出的生产场域，兼具娱乐性及新闻性的画报，传播能力十分可观，能够有效帮助人们理解南洋、建构南洋想象，从而建立起人们的身份认同。 本文将“南洋”的概念放置在二战以后的历史语境中，考察《南洋画报》对“南洋”的想象与建构，观察刊物如何在错综复杂的政治语境下夹缝求存，又如何在建构想象中的南洋之余，通过建构不同的女性形象，呼唤南洋现代性的发生。 The term “Nanyang” is both a geographical and imaginative concept. Due to the deep historical relationship between South East Asia (Nanyang) and China, the meaning of the term is tangled with the Chinese imagination of the region. After the Second World War, the decolonization process made it an urgent issue for people living in the region to redefine their identity and to reconfigure the regional relations and dynamics. The demand for identification required both political and cultural interventions; publications produced during this time thus carry special significance. As a field of knowledge production, Nanyang Monthly was both an intellectual as well as an entertainment project, making it reachable for all kinds of readers. Therefore, not only did it help people in understanding Nanyang, it was also an effective medium in constructing the Nanyang imagination. This paper puts the concept of "Nanyang" in the postwar context to examine the imagination of "Nanyang" by Nanyang Monthly, and the ways the publication calls Into existence a Nanyang modernity.